Model of Slum Settlement Policy in East Lombok, West Nusa Tenggara - Matinni, Nurul; Armansyah, Armansyah (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research is purposed to formulate model of slum settlement policy in Nusa Tenggara Barat Province. Method used in this study is mixed method with data collection method is Purposive Sampling and Analytical Hierarchy Process (AHP). Study discussion is resulting in alternative policy of settlement policy in Nusa Tenggara Barat Province, Indonesia that is: (1) demolition of slum area; (2) opening job vacancy; (3) providing low-cost housing; (4) providing loans from banks; and (5) flats. From these alternative policies, it is aimed to raise standard of living in Nusa Tenggara Barat province, especially in the area of ​​study and eliminating slums area to achieve the correct urban planning.